Levels of Some Pro-inflammatory Cytokines in Pregnant Women with Polycystic Ovary Syndrome - Mohammed A. Taher; Aminah A. Al-Juboori (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2012)
The objective of this study is to determine levels of some pro-inflammatory cytokines (IL-12 and SIL-2R) in pregnant women with polycystic ovary syndrome (PCOS) and also to determine incidence of spontaneous abortion during first trimester in pregnant women with PCOS compared with non-PCOS pregnant women. This Study was performed on (93) women, consisted of: 1- (63) pregnant women during the first trimester, which included:A- (33)PCOS pregnant women and subdivided into the following groups: (20) successful pregnant PCOS, (7) blighted Ovum PCOS and (6) missed abortion PCOS. B- (30) non-PCOS pregnant women, which included: (27) successful pregnant control and (3) non-PCOS pregnant women were withdrawn from this study because of their abortion in first trimester. 2- (30) non-pregnant subjects, which subdivided into the following groups: (18) non-pregnant PCOS and (12) non-pregnant control. Serum luteinizing hormone (LH), testosterone hormone levels and serum pro-inflammatory cytokines [IL-12 and sIL-2R] levels were measured in all subjects. It is found that the incidence of spontaneous abortion {missed(18.2%) and blighted ovum(21.2%)} in first trimester of pregnancy for 33 women which was (39.4%) and it is 3.9 fold higher than incidence of spontaneous abortion {missed(3.3%) and blighted ovum (6.7%)} for 30 non-PCOS pregnant women which was (10%). The LH levels were increasing significantly (P<0.05) in testosterone levels were increasing significantly (P<0.05) in all four PCOS groups when compared with two control groups (pregnant and non-pregnant). The IL-12 levels were elevated in all four PCOS groups when compared with two control groups. The sIL-2R levels were increasing significantly (P<0.05) in spontaneous abortion PCOS group and in non-pregnant PCOS group when compared with pregnant control group. In conclusion rise of some proinflammatory cytokines (IL-12 and sIL-2R) levels in pregnant women with PCOS during the first trimester may be attributed to an endocrine abnormalities and related directly to high levels of testosterone. The rising pro-inflammatory cytokines (IL-12 and sIL-2R) levels of non-pregnant PCOS may be attributed to interactions between the neuroendocrine and immune systems.